Job satisfaction and empowerment of self-employed nurse practitioners: A mixed methods study. Issue 2 (February 2018) - Lyden, Catherine; Sekula, L. Kathleen; Higgins, Barbara; Zoucha, Rick
Abstract : Background and Purpose: Self-employed nurse practitioners (NPs) have been part of the American health care landscape since the 1970s, owning practices throughout the United States. The purpose of this study was to explore and measure the 2 characteristics of job satisfaction and empowerment in self-employed NPs practicing within the 50 states and District of Columbia and to explore factors that influence these characteristics. Methods: A convergent parallel design, mixed methods study, using a survey and semistructured interviews, was completed. The survey included the Misener Job Satisfaction Survey and Conditions of Work Effectiveness Questionnaire II. Conclusions: Self-employed NPs are satisfied and empowered. The more empowered, the higher their level of job satisfaction. Over 40% practiced with full practice authority in a rural location, and 50% had over 10 years of experience as both an RN and NP. Their experience in private practice was explored further in the interviews. Implications for practice: This study identifies barriers to job satisfaction and empowerment in self-employed NPs, including physician oversight and lack of business management education. Continuing work to remove restricted and reduced state regulatory environments and to provide education on business management may increase the number of NPs in private practice, expanding access to health care in the United States.